Energy, Equipment and Cost Savings by Using a Membrane Unit in an Amine‐Based Absorption Process for CO2 Removal. Issue 8 (10th June 2013) - Song, Shankui; Esche, Erik; Stünkel, Steffen; Brinkmann, Torsten; Wind, Jan; Shishatskiy, Sergey; Wozny, Günter
Abstract: A hybrid system consisting of a membrane unit and an amine‐based process for CO2 removal in the oxidative coupling of methane is investigated experimentally and in simulations. Absorption processes with two different absorbents for removing 90 % of CO2 from the feed stream are regarded as benchmarks and compared to the membrane process with respect to potential energy, equipment, and cost reductions. The results show that a membrane unit using polyimide could assist with CO2 capture and lead to a reduction of the consumed energy per kilogram of CO2 by 40 % and also reduce the size of the absorption columns. Alternative processes with a two‐step membrane cascade to enhance the recovery of product ethylene are also discussed. Abstract : Ethylene can be directly produced through oxidative coupling of methane instead of cracking process, but a CO2 separation section is necessary in the downstreaming. A hybrid system of membrane unit and chemical absorption process is presented that provides energy and cost savings compared to the commonly used CO2 removal process.